2007
DOI: 10.1124/mol.107.040568
|View full text |Cite
|
Sign up to set email alerts
|

Are α9α10 Nicotinic Acetylcholine Receptors a Pain Target for α-Conotoxins?

Abstract: The synthetic ␣-conotoxin Vc1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 18 publications
3
104
1
Order By: Relevance
“…We have previously shown that Vc1.1 is anti-allodynic in neuropathic pain models when administered intramuscularly, and that sustained reversal of allodynia appears due to GABA B -receptor-dependent inhibition of Ntype Ca 2+ channels because it is reversed by a selective GABA B -receptor antagonist (Klimis et al 2011). Furthermore, we observed no reversal of allodynia with peripheral administration of two analogs of Vc1.1, vc1a and [P60]Vc1.1 that exhibited no activity at GABA B receptor/N-type Ca 2+ channels but full activity at α9α10 nAChRs, suggesting that antagonism of α9α10 is not a requisite for anti-allodynia (Nevin et al 2007;Callaghan et al 2008). However, Vc1.1, AuIB and MII have markedly different (> 1000-fold) potencies for GABA B receptors/N-type calcium channels, with MII being nearly inactive.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We have previously shown that Vc1.1 is anti-allodynic in neuropathic pain models when administered intramuscularly, and that sustained reversal of allodynia appears due to GABA B -receptor-dependent inhibition of Ntype Ca 2+ channels because it is reversed by a selective GABA B -receptor antagonist (Klimis et al 2011). Furthermore, we observed no reversal of allodynia with peripheral administration of two analogs of Vc1.1, vc1a and [P60]Vc1.1 that exhibited no activity at GABA B receptor/N-type Ca 2+ channels but full activity at α9α10 nAChRs, suggesting that antagonism of α9α10 is not a requisite for anti-allodynia (Nevin et al 2007;Callaghan et al 2008). However, Vc1.1, AuIB and MII have markedly different (> 1000-fold) potencies for GABA B receptors/N-type calcium channels, with MII being nearly inactive.…”
Section: Discussionmentioning
confidence: 62%
“…Vc1.1 and RgIA are both potent antagonists of α9α10 nAChRs, suggesting this may be the anti-allodynia target (Vincler et al 2006). However, MII and AuIB are both devoid of activity at α9α10 nAChRs (McIntosh et al 1999;Callaghan et al 2008;Azam and McIntosh 2009;Callaghan and Adams 2010;Klimis et al 2011) and other -conotoxin analogues that act on these nAChRs fail to inhibit allodynia (Nevin et al 2007). Moreover, 910 nAChRs show very limited tissue distribution, being expressed predominantly in the olivochochlear system (Vetter et al, 2007) and their role in sensory nerve function is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of nerve function retained Nevin et al, 2007 Rg1A Partially reverses mechanical allodynia in several neuropathic models after intramuscular dosing. human sural nerve to nicotine (Lang et al, 2005).…”
Section: Very Weak ␣9␣10mentioning
confidence: 99%
“…A more plausible hypothesis was forwarded by Vincler and McIntosh (2007), who suggested the analgesic efficacy of ␣-conotoxins that inhibit ␣9␣10 nAChRs was due to inhibition of immune cell migration to injured nerves, although it remains to be determined whether this process is modulated by ␣9␣10 nAChRs. However, two analogs of Vc1.1, Vc1a and [P6O]Vc1.1, retain full activity ␣9␣10 nAChRs but lose activity at other targets (see below) and fail to reverse allodynia in a neuropathic pain model (Nevin et al, 2007). Conversely, ␣-AuIB and ␣-MII are efficacious in a neuropathic pain model but do not inhibit ␣9␣10 nAChRs (Klimis et al, 2011).…”
Section: Very Weak ␣9␣10mentioning
confidence: 99%
“…Nicotine was used for the ␣7 nAChRs to avoid the partial agonist effect of choline because of the potential breakdown of ACh. Toxins and agonists were applied as described (15) or by the OpusXpress drug delivery system (18). Peak current amplitudes were measured before and following 180 or 200 s incubation of the GID analogues.…”
Section: Functional Characterizationmentioning
confidence: 99%